Applying the computer in the solution of electrical engineering problems - Escoto, Miguel T. Jr (Philippine Engineering Journal)
This paper lists some of the potential areas where computers might be applied in the solution of electrical engineering problems. Specifically, it briefly describes the goals that were used as guides in the development of a computer-oriented circuit analysis course (COCA) offered at the University of the Philippines, Department of Electrical Engineering. An example program demonstrates some points of interest pertinent to the applications of microcomputers for digital computations in basic circuit theory.